Analysis on Reading and Writing Section of Test Items in 2009/2010 English National Final Examination (UAN) for Junior High School Students - Siti Musarokah; Dwi Anggani Linggar Bharati (Universitas PGRI Semarang, 2010)
ABSTRACT This paper attempts to analyze the test items in the English National Final Examination (UAN) for Junior High School Students in the academic year 2009/2010. This study aims at analyzing the compatibility of the test items of package A in reading and writing section of English National Final Examination for Junior High School Students with the standard of graduate competence and the cognitive domains used in the test. The data were collected by using documentary method, while in analyzing the data the writers focused on matching the compatibility of the test items with the Standard of Graduate Competence and identifying the cognitive domain used. From the analysis, it was found that the test items of package A in reading and writing section of English National Final Examination 2009/2010 were in line with the Standard of Graduate Competence (SKL) arranged by the government. The cognitive domains in reading section mostly used level of comprehension. The cognitive domains in writing section used the application and the synthesis level. ?é?á Key words: analysis, test items, national final examination